Analytical Hierarchy Process for Regional Development Priority in Maluku Province, Indonesia - Lia Amellya Larasati; Nur Medisyanning Khoiruluswati; Rizki Rahmi Aliyya; Unggul Widyanarko; Ratih Fitria Putri (ASEAN Journal on Science and Technology for Development, 2019)
Maluku is one of the provinces of the eastern part of Indonesia, consisting of 11 regencies. The Maluku branch of Statistics Indonesia reported in 2018 that in 2013–2018 the number of poor people in Maluku's rural areas increased by 1,970. Concurrently, the number of poor people in urban areas decreased by around 6,070 people. This fact showed that development in Maluku Province hadn't been implemented effectively and equally. This study aimed to determine the development priority in Maluku Province using the Analytical Hierarchy Process method. The determination of priorities was based on three aspects in the human development index concept, namely education, health, and economy. Data from Statistics Indonesia on life expectancy, mean years of schooling, expected years of schooling, and per capita expenditure were the indicators were used as the indicators in this study. The results showed that there were 10 regencies with a high level of priority, with the exception being Ambon City, which had a low-level priority. Classification of regencies showed that there was a disparity between them. These findings can help to inform future development designs in Maluku Province.